(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the inclusion of feather meal (FM) in diets reduced in crude protein (CP) and amino acids (AA) for meat-type quails. 240 male meat-type quails were used in the phases from 8 to 21 days and 8 to 35 days of age, distributed in a completely randomized design, in a 2 x 3 factorial scheme (two diets: positive control (PC) and negative control (NC) reduced in CP and AA in relation to PC x three levels of inclusion of FM: 0, 5 and 10%), totaling 6 treatments, with 4 repetitions of 10 quails per plot. There was an interaction (P<0.05) between the inclusion of FM and diets for feed consumption in the 8 to 21 days phase, as well as an effect of the inclusion of FM and diets for weight gain and feed conversion. In the period from 8 to 35 days there was no effect (P> 0.05) of the interaction between the factors, but an effect (P<0.05) of the inclusion of FM for feed consumption and for the inclusion of FM and the diets for weight gain and feed conversion. The use of FM at any level used did not affect (P>0.05) the carcass variables, except for the thigh + drumstick yield (P<0.05), which was better for NC. FM can be used in up to 5%, without causing damage to the performance of quails. The NC diet with reduction of CP and AA does not present a good strategy to improve the performance of quails.